Vitamin D as an intervention for improving quadriceps muscle strength in patients after anterior cruciate ligament reconstruction: study protocol for a randomized double-blinded, placebo-controlled clinical trial - Michael Tim-yun Ong; Xiaomin Lu; Ben Chi-yin Choi; Siu-Wai Wan; Qianwen Wang; Gene Chi-wai Man; Pauline Po-yee Lui; Daniel Tik-Pui Fong; Daniel Kam-wah Mok; Patrick Shu-hang Yung (Trials, 2024)
Abstract Background The goal of anterior cruciate ligament reconstruction (ACLR) is to restore the preinjury level of knee function to return to play (RTP). However, even after completing the rehabilitation programme, some patients may have persistent quadriceps muscle weakness affecting knee function which ultimately leads to a failure in returning to play. Vitamin D has been long recognized for its musculoskeletal effects. Vitamin D deficiency may impair muscle strength recovery after ACLR. Correcting vitamin D levels may improve muscle strength. Methods This is a double-blinded, randomized controlled trial to investigate the effects of vitamin D supplementation during the post-operative period on quadriceps muscle strength in anterior cruciate ligament (ACL)-injured patients. Patients aged 18–50 with serum vitamin D < 20 ng/ml, unilateral ACL injury, > 90% deficit in total quadriceps muscle volume on the involved leg compared with uninvolved leg, Tegner score 7 + , and no previous knee injury/surgery will be recruited. To assess patient improvement, we will perform isokinetic and isometric muscle assessments, ultrasound imaging for quadriceps thickness, self-reported outcomes, KT-1000 for knee laxity, biomechanical analysis, and Xtreme CT for bone mineral density. To investigate the effect of vitamin D status on quadriceps strength, blood serum samples will be taken before and after intervention. Discussion Patients with low vitamin D levels had greater quadriceps fibre cross-sectional area loss and impaired muscle strength recovery after ACL. The proposed study will provide scientific support for using vitamin D supplementation to improve quadriceps strength recovery after ACLR. Trial registration ClinicalTrials.gov NCT05174611. Registered on 28 November 2021.